A Qualitative Meta-Synthesis of English Education Studies Regarding Development of Taiwanese Students’ Skills in the University Level - Maravilla, Wes Harven G.; Maming, Jimmy Bernabe; Toring, Kimberly N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Technology is crucial to language learning particularly the English language and entails enormous potential. It is also clear that the evolution of technology in the present times has a significant impact on how well foreign language learners acquire their new language. As a result, the current study's objective is to give a meta-synthesis of research findings on student development activities published in prestigious academic journals. Eight 2020–2022 studies examined English language learning innovations. For a systematic review, the studies were grouped using the Critical Skills for Evaluation Program (CASP) checklist and PRISMA 2020 flow diagram. Thematic analysis identified four primary themes were: (1) Using multimedia technology for speaking, (2) Designing and delivering writing courses, (3) Internet-based listening and reading pedagogy, (4) Attending cramming classes. The study's meta-theme, dimensions of a student development activity, emerged. It is advised that teachers and students consider the following aspects of the student development activity in their regular English language study.